An Audit of Renal Clinical Pharmacist Provided Drug Information Services to Nephrology Department - Sridhar, Sathvik Belagodu; Khan, Shoukath Ali; Shetty, Manjunath S (Indian Journal of Pharmacy Practice)
Background: Clinical pharmacy services in various ambulatory care settings are well-defined and documented. Nevertheless, data addressing clinical pharmacist-provided drug information services to the nephrology department are very limited. The aims of our study were to evaluate the type and quality of clinical pharmacist provided drug information services to the nephrology department. Methodology: The research clinical pharmacist participated in nephrology ward rounds for six days in a week along with an academic renal clinical pharmacist. Any medication related queries requested by the nephrologists or by other healthcare nephrology members were received and attended as per the modified systematic approach for the provision of drug information. Subsequently, the feedback information was provided to the concerned enquirer. The quality of all drug information services provided was evaluated by using drug information quality assurance assessment questionnaire. Results: Overall, 97 drug information requests were received and answered during the study period. Majority of the requests (n=72, 74.22%) were related to the management of the patient under nephrology care and good number of the requests were related to medication dosage (n=42, 43.29%) followed adverse drug reactions (n=22, 22.68%). The preponderance of the requests (n=54, 55.67%) required up to 15 minutes of search from various drug information resources and most of these requests (n=61, 62.88%) were answered verbally with the aid of single reference (n=48, 49.48%). Majority (n=62) of the drug information requests were graded as excellent. Conclusion: Our study confirms the promising role of a renal pharmacist in drug therapy management of really impaired patients and participation of renal clinical pharmacist in the regular ward rounds could be the main reason for both good number and quality of drug information provided.
Keywords: Drug Information; Clinical Pharmacist; Renal Pharmacy; Quality Assurance; Pharmaceutical Care